2019
DOI: 10.31349/revmexfis.65.307
|View full text |Cite
|
Sign up to set email alerts
|

Multi-TeV flaring in nearby high-energy blazars: A photohadronic scenario

Abstract: Blazars are a subclass of AGN and flaring in multi-TeV gamma-ray seems to be the major activity in high energy blazars a subgrup of blazars. Flaring is also unpredictable and switches between quiescent and active states involving different time scales and fluxes. While in some high energy blazars a strong temporal correlation between X-ray and multi-TeV gamma-ray has been observed, outbursts in some other have no low energy counterparts and explanation of such extreme activity needs to be addressed through dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 93 publications
(159 reference statements)
0
46
0
Order By: Relevance
“…By assuming that the multi-TeV emission in the HBLs are due to the photohadronic interaction in the jet (Sahu 2019;Sahu et al 2017b), a simple relation between the observed VHE spectrum and the intrinsic spectrum is derived. We assume that during the VHE emission period, the Fermi accelerated protons having a power-law spectrum (Dermer & Schlickeiser 1993), dN/dE ∝ E −α (the power index α ≥ 2) , interact with the background seed photons in the jet to produce the ∆-resonance (pγ → ∆ + ), which subsequently decays to γ-rays via intermediate π 0 and to neutrinos through π + .…”
Section: Photohadronic Modelmentioning
confidence: 99%
“…By assuming that the multi-TeV emission in the HBLs are due to the photohadronic interaction in the jet (Sahu 2019;Sahu et al 2017b), a simple relation between the observed VHE spectrum and the intrinsic spectrum is derived. We assume that during the VHE emission period, the Fermi accelerated protons having a power-law spectrum (Dermer & Schlickeiser 1993), dN/dE ∝ E −α (the power index α ≥ 2) , interact with the background seed photons in the jet to produce the ∆-resonance (pγ → ∆ + ), which subsequently decays to γ-rays via intermediate π 0 and to neutrinos through π + .…”
Section: Photohadronic Modelmentioning
confidence: 99%
“…The photohadronic model of Sahu et al [15,16,21,22] can explain the flaring events from HBLs very well and it relies on the standard interpretation of the leptonic model discussed above to explain both low and high energy peaks by synchrotron and SSC photons respectively as in the case of any other AGN.…”
Section: The Modelmentioning
confidence: 99%
“…Using the scaling condition of Eq. (1), the photon density in the inner region can be expressed in terms of the observed flux [15,16].…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations